Pemanfaatan Limbah Sayuran dan Buah-buahan Sebagai Bahan Pupuk Organik Cair di Desa Pangkalan Batang Melalui Program KUKERTA Universitas Riau - Bunari Bunari; Ratih Purnama Sari; Dita Asrilla Putri; Dini Oktafiani; Dwi Puspita; Widya Triananda; Pika Desmayu Putri; Istiqomah Istiqomah; Ardha Wildana; Muhammad Reihan; Muhammad Aziz (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This service program aims to help the Pangkalan Batang Village community, the Women Farmers Group (KWT), and Dasa Wisma hamlet manufacture by creating and using an organic liquid fertilizer that can be used on plants. Pangkalan Batang Village has excellent potential in farming; the surrounding community has sufficient land to be used as agricultural land. This program demonstrated that partners understood how to make and apply liquid organic fertilizer. This service program had succeeded in increasing knowledge for the community, the Women Farmers Group (KWT), and Dasa Wisma in creating and applying the liquid organic fertilizer. Some also continue to make organic fertilizers that will be used in plants without using chemical-based organic fertilizers.